EP004/#741 DNA methylation landscape as a potential player in acquired-drug resistance in ovarian cancer. (4th December 2022) - Silva, Romina; Glennon, Kate; Metoudi, Michael; Moran, Bruce; Salta, Sofia; Slattery, Karen; Treacy, Ann; Martin, Terri; Shaw, Jacqui; Doran, Peter; Lynch, Lydia; Jeronimo, Carmen; et al.
Abstract : Objectives: Development of therapeutic resistance is a major cause of mortality in high-grade serous ovarian cancer (HGSOC), thus a better understanding of acquired resistance mechanisms is needed. This study aimed to investigate how epigenomic events might be associated with acquired-drug resistance in HGSOC patients. Methods: Methylation and gene expression differences between primary platinum-sensitive (n=32) and recurrent acquired-resistant samples (n=28) was explored using a HGSOC dataset. High resolution melting was used to validate results using epithelial ovarian cancer cell lines and HGSOC tumours. A CRISPR-Cas9 approach was used to investigate the effects of DNA methylation editing in vitro. Plasma samples from HGSOC patients (n=17) and age-matched healthy controls (n=20) were used to investigate longitudinal methylation dynamics via droplet digital PCR. Results: Comparison of methylation and gene expression analysis identified several genes, known to be involved in diverse immune and chemoresistance-related pathways, that significantly differentiated between paired platinum-sensitive and acquired-resistant HGSOC samples, with three genes displaying the most consistent methylation changes (PDCD1, NKAPL, APOBEC3A). A CRISPR-Cas9 approach was used to interrogate the effects of APOBEC3A and NKAPL promoter methylation editing on platinum sensitivity, with demethylation of NKAPL promoter being associated with increased platinum sensitivity. Hypermethylation of NKAPL and APOBEC3A were detected in 46% and 69%, respectively, of plasma samples from women with relapsed HGSOC. Conclusions: Promoter methylation has been identified as potentially involved in HGSOC drug resistance. Further research is warranted to understand the future use of these methylation patterns as prognostic/predictive markers in the OC clinical setting.